(untitled) - Mehmet Aykut Erk; Sunay Fırat (Psikiyatride Güncel Yaklaşımlar, 2020)
The aim of this study was to develop a scale (measurement tool) to evaluate the effect of changing socialization and relational satisfaction sources on Twitch viewers with the ever-evolving information technologies and the main motivations of the viewers who watch the streams, donate to the streamers and become a community. The population of the study was consisted of the Top 100 Turkish speaking streamers with the highest numbers of viewers according to the websites such as Socialblade and Twitch metrics that produce statistics about streams, streamers and viewers. Study group was consisted of 318 viewers who have filled the study form researchers shared on the Twitch platform. Sociodemographic Data Collection Form and Twitch Viewer Motivation Scale have been conducted to participants. According to results of Kaiser Meyer-Olkin (KMO) and Bartlett’s Test of Sphericity, it has been found that there is a significance ratio over 0.80 between items of the scale. Factor loadings of the remaining items range from 0.615 to 0.766. Cronbach’s Alpha reliability coefficients of each factor were found to be between 0.67-0.82. Consequently this scale is able to illuminate-by the mean of reliability- the treatment of the behavior which is accepted as dependence and provide prevention.